Quantum Computers - Roy, Megha; Santra, Soumen; Majumdar, Sarasij (International Journal of Computer Sciences and Engineering, 2025)
Computers have become an indispensible part of our life. Advancements in the field of technology have led to smaller and more compact computers, while their processing power has increased. However, with parts getting smaller and more compact, quantum physics are making things a bit problematic. Transistors act like switches, either allowing electrons to pass through or blocking their passage. Transistors are already almost as small as atoms. Electrons will eventually be able to transfer themselves to the other side of the blocked passage via a process called quantum tunneling, making transistors useless. Classical computers and the way it works stop making sense in the quantum realm. A possible solution to this problem could be quantum computers, which takes advantage of quantum principles to work. In this paper, an overview of quantum computers, their working principles and the basics of the math behind such computers have been discussed. The future scope of such a computer, problems associated with implementing it as well as the problems to be dealt with in case a scalable quantum computer is built is also provided.